A silver-inserted zinc rhodium oxide and bismuth vanadium oxide heterojunction photocatalyst for overall pure-water splitting under red light. Issue 8 (9th December 2015) - Kobayashi, Ryoya; Kurihara, Kazuki; Takashima, Toshihiro; Ohtani, Bunsho; Irie, Hiroshi
Abstract : We have prepared a solid-state heterojunction photocatalyst, in which zinc rhodium oxide (ZnRh2 O4 ) and bismuth vanadium oxide (Bi4 V2 O11 ) as hydrogen (H2 ) and oxygen (O2 ) evolution photocatalysts, respectively, were connected with silver (Ag, ZnRh2 O4 /Ag/Bi4 V2 O11 ). Abstract : We have prepared a solid-state heterojunction photocatalyst, in which zinc rhodium oxide (ZnRh2 O4 ) and bismuth vanadium oxide (Bi4 V2 O11 ) as hydrogen (H2 ) and oxygen (O2 ) evolution photocatalysts, respectively, were connected with silver (Ag, ZnRh2 O4 /Ag/Bi4 V2 O11 ). ZnRh2 O4 /Ag/Bi4 V2 O11 was able to photocatalyze overall pure-water splitting under red-light irradiation with a wavelength of 700 nm. On the basis of the analogy with a solid-state heterojunction photocatalyst composed of ZnRh2 O4, defective silver antimonate (Ag1− x SbO3− y ), and Ag (R. Kobayashi et al., J. Phys. Chem. C, 2014, 118, 22450–22456), we consider that the overall water-splitting performance of the ZnRh2 O4 /Ag/Bi4 V2 O11 photocatalyst was derived from the photoproduced holes that were generated in the valence band (VB) of Bi4 V2 O11 contributing to O2 liberation and the photoexcited electrons that were generated in the conduction band (CB) of ZnRh2 O4 contributing to H2 liberation. Importantly, Ag possibly acts as a solid-state electron mediator for the transfer of electrons from the CB of Bi4 V2 O11 to the VB of ZnRh2 O4 .